2007
DOI: 10.1002/app.26832
|View full text |Cite
|
Sign up to set email alerts
|

Toughening and compatibilization of polyphenylene sulfide/nylon 66 blends with SEBS and maleic anhydride grafted SEBS triblock copolymers

Abstract: In this study, styrene-b-ethylene/butylene-bstyrene triblock copolymer (SEBS) and maleic anhydride grafted SEBS (SEBS-g-MA) were used as compatibilizers for the blends of polyphenylene sulfide/nylon 66 (PPS/PA66). The mechanical properties, including impact and tensile properties and morphology of the blends, were investigated by mechanical properties measurements and scanning electron microscopy. Impact measurements indicated that the impact strength of the blends increases slowly with elastomer (SEBS and SEB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…It was demonstrated that the so-compatibilized interface in PPS/LCP blends significantly contributes to the enhancement of tensile properties and impact strength. 10 The second group of PPS blends is formed with conventional engineering plastics with thermal stability between 100-140 1C for long usage such as crystalline polyamide (PA) [11][12][13] and poly(ethylene terephthalate) (PET), [14][15][16] and amorphous poly(phenylene ether) 17 and polycarbonate (PC). 18 It is reported that (20/80) PPS/PA4,6 (T m of PA4,6¼295 1C) blends have a miscible region, which appears under a high shear rate at 310-320 1C 13 although the solubility parameter of PPS is extremely high (12.5 (cal cm À3 ) 0.5 ) compared with other polymers and this makes it difficult for PPS to have miscibility with other polymers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that the so-compatibilized interface in PPS/LCP blends significantly contributes to the enhancement of tensile properties and impact strength. 10 The second group of PPS blends is formed with conventional engineering plastics with thermal stability between 100-140 1C for long usage such as crystalline polyamide (PA) [11][12][13] and poly(ethylene terephthalate) (PET), [14][15][16] and amorphous poly(phenylene ether) 17 and polycarbonate (PC). 18 It is reported that (20/80) PPS/PA4,6 (T m of PA4,6¼295 1C) blends have a miscible region, which appears under a high shear rate at 310-320 1C 13 although the solubility parameter of PPS is extremely high (12.5 (cal cm À3 ) 0.5 ) compared with other polymers and this makes it difficult for PPS to have miscibility with other polymers.…”
Section: Introductionmentioning
confidence: 99%
“…19 Among various studies on PPS/PA blends, PA66 is the most intensively investigated because of its superior mechanical properties, especially when exposed to solvents at elevated temperatures. 11,12,19 It was observed that the Izod impact strength and elongation at break of the PPS/PA66 are increased by moisture uptake. 19 This binary PPS/PA66 system has been further developed into ternary systems by the addition of another component such as a compatibilizer to efficiently improve mechanical properties, 11,12 an internal lubricant poly(tetrafluoroethylene) to increase the wear resistance, 20 glass fiber 21 and carbon nanotubes 22 to reinforce the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many approaches have been proposed to overcome these disadvantages of PPS. To modify PPS by physical blending or alloying with other polymers or with other reinforcement materials is the most common and widespread method in industrial and academic domains currently …”
Section: Blendingmentioning
confidence: 99%
“…Additionally, Tand et al have studied the N6/Polyphenylene Sulfide (N6/PPS) blend using SEBS-g-MA as the coupling agent. Their results indicated that the impact strength increased with the weight fraction of SEBS-g-MA increase, especially when the fraction was between 20% and 50% [23]. Yang et al have studied the fracture behavior of N66/TiO 2 composites.…”
Section: Studies On Mechanical Properties Of the Nylon Compositesmentioning
confidence: 99%